Optimalisasi Penguatan Program Stunting di Rumah Sakit - Lestari, Puji; Hariyati, Rr.Tutik Sri; Wildani, Andi Amalia; Widiasari, Widiasari; Yetti, Krisna (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This research aims to describe the implementation of planned changes to improve the implementation of stunting risk discovery, through the preparation of guidelines for stunting and wasting risk nursing care. The research method used is a case report which includes problem identification, problem analysis, plan of action (POA), implementation and evaluation activities. Data collection was carried out using interview guides, questionnaires. The results of the research show that the implementation of the planning function in implementing the stunting program is not yet optimal, so guidance is needed so that implementation is more optimal. In conclusion, the preparation of stunting risk nursing care guidelines and clinical pathways is a solution to the problem. PoA implementation was carried out using Kurt Lewin's planned change approach. Keywords: Nursing care, Clinical pathway, Stunting